B1 homogeneity of breast MRI using RF shimming with individual specific values in volunteers simulating patients after mastectomy. (November 2016) - Abe, Takayuki
Background: Magnetic resonance imaging (MRI) using a 3-T MRI scanner is now widely used for clinical examinations. However, B1 inhomogeneity becomes larger with MRI scanners using 3-T and higher. It especially becomes a problem in the breast. To improve B1 homogeneity, a RF shimming technique has been developed. Purpose: To evaluate the B1 homogeneity of breast MRI using RF shimming with individual specific values for subjects after mastectomy. Material and Methods: The subjects are healthy female volunteers who underwent normal breast imaging, followed by imaging of one breast while the other breast was bound tightly to the chest by bleached cotton cloths (simulating volunteers after mastectomy). B1 mappings were performed with RF shimming using two techniques: (i) optimized fixed value; and (ii) individual specific values using a 3-T MRI scanner. The means and standard deviations of the B1 maps for all slices in the breast were measured and compared between the fixed value and the individual specific value cases. Results: For normal volunteers, the breast B1 variation was not statistically significantly different between the RF shimming techniques. For volunteers after simulated surgery, the breast B1 variation was (1.02 ± 0.29) with the fixed value and (0.98 ± 0.22) with the individual specific value ( P < 0.01). With the individual specific optimization, B1 variation for all slices in the breast was improved for volunteers after simulated surgery. Conclusion: RF shimming with individual specific values has the potential to improve the B1 homogeneity of breast MRI in patients after mastectomy.